2016
DOI: 10.1021/acschembio.6b00575
|View full text |Cite|
|
Sign up to set email alerts
|

Designed Small-Molecule Inhibitors of the Anthranilyl-CoA Synthetase PqsA Block Quinolone Biosynthesis in Pseudomonas aeruginosa

Abstract: The Gram-negative bacterial pathogen Pseudomonas aeruginosa uses three interconnected intercellular signaling systems regulated by the transcription factors LasR, RhlR, and MvfR (PqsR), which mediate bacterial cell–cell communication via small-molecule natural products and control the production of a variety of virulence factors. The MvfR system is activated by and controls the biosynthesis of the quinolone quorum sensing factors HHQ and PQS. A key step in the biosynthesis of these quinolones is catalyzed by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 78 publications
1
47
0
Order By: Relevance
“…Interference with the function of MvfR results in lowered virulence by P. aeruginosa (52,53). Consequently, MvfR has advanced to a target for the development of strategies to combat P. aeruginosa infections.…”
Section: Discussionmentioning
confidence: 99%
“…Interference with the function of MvfR results in lowered virulence by P. aeruginosa (52,53). Consequently, MvfR has advanced to a target for the development of strategies to combat P. aeruginosa infections.…”
Section: Discussionmentioning
confidence: 99%
“…In summary, the crystal structures of PqsA NTD discussed here broaden our knowledge of anthranilate‐CoA ligases in general. The structural insight into the active site architecture of PqsA NTD might also help rationally guided improvement of the only moderately active AMP‐based sulfonyladenosine PqsA inhibitors recently published by Ji et al., and this in turn might ultimately lead to alternative therapeutic approaches targeting the quinolone signaling cascade of P. aeruginosa .…”
Section: Resultsmentioning
confidence: 98%
“…It has previously been shown that AQ production in P. aeruginosa can be strongly reduced by halogenated anthranilate derivatives: this is a consequence of incorporation of these compounds by PqsA, probably followed by inhibition of one of the downstream steps in HHQ/PQS biosynthesis. The most efficient inhibitor was 6‐fluoroanthranilate (6FABA), which was turned over to the corresponding thioester with efficiency similar to that of the natural substrate anthranilate but abolished PQS production completely when applied at concentrations in the millimolar range . We therefore performed cocrystallization experiments with 6FABA/ATP⋅Mg 2+ and were able to obtain diffraction data from a crystal in form 1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations